Gradient boron carbide composite material with double-layer structure as well as preparation method and application of gradient boron carbide composite material
By using a gradient structure boron carbide composite material in the double-layer structure elastic-resistant products, combined with the deposit of pyrolytic carbon on the carbon fiber cloth and high-temperature heat treatment, the problems of low hardness and elastic modulus of the back plate of the existing elastic-resistant products are solved, and higher elastic resistance and lower self-weight are achieved.
Patent Information
- Application Number
- CN202510063821.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The backplate of existing double-layer structure elastic-resistant products is mainly fiber-toughened polymer-based composite materials, with low hardness and elastic modulus, resulting in poor elastic resistance. There is a lack of research on the gradual increase in fracture toughness of the backplate.
The double-layer structural gradient boron carbide composite material is used, including boron carbide ceramic layer and carbon fiber toughened boron carbide composite material layer. The fracture toughness of the carbon fiber toughened boron carbide composite material layer is gradually increased.
Effectively avoid the separation of the back plate and the panel after the elastic body penetrates the panel, significantly improve the anti-elastic effect of the double-layer anti-elastic structure, and reduce the self-weight of the anti-elastic material.
Smart Images

Figure CN119841655A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-bullet materials, and in particular relates to a double-layer structure gradient boron carbide composite material and a preparation method and application thereof. Background Art
[0002] The sea surface environment is open, and ships cannot dodge when attacked by anti-ship missiles. They can only rely on their armor and external anti-ballistic products to passively resist. With the development of anti-ship missile warhead charging technology, the high-speed fragments formed by the warhead explosion have strong penetration capabilities. Increasing the structural thickness of the ship can improve the ship's anti-penetration capability to a certain extent, but it will increase the weight of the hull and weaken the ship's maneuverability. In order to take into account the ship's anti-ballistic performance and maneuverability, it is urgent to develop anti-ballistic products with strong anti-penetration capabilities and low dead weight.
[0003] Ceramics such as alumina, boron carbide, titanium diboride and silicon carbide have a much lower density than steel and are characterized by high hardness and strength. Bulletproof products made from such ceramics can quickly passivate, erode and break projectiles while resisting projectile penetration. However, due to the high brittleness and low tensile strength of such ceramics, they are unable to absorb a large amount of energy when resisting projectile penetration, resulting in poor bulletproof effects. Therefore, in actual applications, such ceramics are usually used as panels and laminated with backing plates with high fracture toughness to form double-layer bulletproof products.
[0004] The backboard of existing double-layer bullet-proof products is mainly fiber-reinforced polymer-based composite materials. Such composite materials can significantly improve the bullet-proof effect of double-layer bullet-proof products due to their high fracture toughness. Recent studies have shown that while the backboard has high fracture toughness, improving the hardness, strength and elastic modulus of the backboard can further improve the bullet-proof effect of double-layer bullet-proof products and reduce the back convexity of the bullet-proof material. However, due to its low hardness and elastic modulus, the polymer-based composite backboard does not have the ability to further improve the bullet-proof effect of double-layer bullet-proof products. Through theoretical calculations, it is known that when the hardness and strength of the backboard are improved, if the fracture toughness of the backboard can be gradually increased, the bullet-proof effect of the bullet-proof product will have greater room for improvement. At present, there are no research reports on the gradual increase in the fracture toughness of the backboard. Summary of the invention
[0005] In order to solve the problems of the background technology, the present invention provides a double-layer structure gradient boron carbide composite material and a preparation method and application thereof.
[0006] The technical solution of the present invention is as follows:
[0007] The present invention provides a double-layer structure gradient boron carbide composite material, comprising a boron carbide ceramic layer and a carbon fiber toughened boron carbide composite material layer, and formed by combining boron carbide deposition layers;
[0008] The carbon fiber toughened boron carbide composite material layer is composed of multiple groups of composite carbon fiber cloths, each group of composite carbon fiber cloths is composed of multiple carbon fiber cloths and pyrolytic carbon and boron carbide deposited on the surface of the carbon fiber cloths in sequence, and the thickness of the pyrolytic carbon increases in a direction away from the boron carbide ceramic layer in groups.
[0009] Furthermore, the thickness of the boron carbide deposition layer, i.e., the boron carbide deposited on the pyrolytic carbon on the surface of the carbon fiber cloth, is 60 to 90 μm.
[0010] In addition, the thickness of the pyrolytic carbon deposited on the surface of the carbon fiber cloth is 80 to 200 nm.
[0011] The thickness of the double-layer structure gradient boron carbide composite material is 26.5-29.8 mm, wherein the thickness of the boron carbide ceramic layer is 20 mm, and the thickness of the carbon fiber toughened boron carbide composite material layer is 6.5-9.8 mm.
[0012] The composite carbon fiber cloths are in 4 groups, and each group of composite carbon fiber cloths includes 6 to 9 carbon fiber cloths.
[0013] Furthermore, the thickness of the pyrolytic carbon in the four groups of composite carbon fiber cloths, along the direction away from the boron carbide ceramic layer, is 80-110 nm, 110-140 nm, 140-170 nm, and 170-200 nm, respectively.
[0014] The present invention also provides a method for preparing the double-layer structure gradient boron carbide composite material, comprising the following steps:
[0015] (1) After chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, the cloth is placed in argon gas and subjected to high temperature heat treatment at 1760-1840° C. for 60-100 min to obtain a first composite carbon fiber cloth, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 80-200 nm;
[0016] (2) taking a first composite carbon fiber cloth having the same pyrolytic carbon thickness as a group, laying a plurality of groups of first composite carbon fiber cloths on the boron carbide ceramic layer having stripes in the order of increasing pyrolytic carbon thickness in a direction away from the boron carbide ceramic layer, and compacting them to obtain a preform;
[0017] (3) Chemical vapor deposition of boron carbide on the preform to obtain a double-layer structured gradient boron carbide composite material.
[0018] Specifically, the operations are as follows:
[0019] (1) The first group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1760 to 1780° C. for 60 to 70 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 80 to 110 nm;
[0020] The second group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1780 to 1800° C. for 70 to 80 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 110 to 140 nm;
[0021] The third group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1800 to 1820° C. for 80 to 90 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 140 to 170 nm;
[0022] The fourth group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1820 to 1840° C. for 90 to 100 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 170 to 200 nm;
[0023] (2) laying four groups of first composite carbon fiber cloths in order of increasing pyrolytic carbon thickness in a direction away from the boron carbide ceramic layer, and pressing them to obtain a preform;
[0024] (3) Chemical vapor deposition of boron carbide on the preform, wherein the thickness of the boron carbide is 60 to 90 μm, thereby obtaining a double-layer structured gradient boron carbide composite material.
[0025] Wherein, in the step (2), the cross section of the stripe is an isosceles trapezoid, the height of the isosceles trapezoid is 0.5-0.8 mm, the length of the upper side is 0.3-0.5 mm, and the length of the lower side is 0.9-1.2 mm.
[0026] The present invention also provides an application of the double-layer structure gradient boron carbide composite material in anti-bullet materials.
[0027] Beneficial Effects
[0028] The method provided by the present invention not only completes the preparation of the carbon fiber toughened boron carbide composite material layer, but also realizes the firm bonding of the boron carbide ceramic layer and the carbon fiber toughened boron carbide composite material layer. The obtained double-layer structure gradient boron carbide composite material can effectively avoid the separation of the back plate and the face plate when the projectile penetrates the face plate (i.e., the boron carbide ceramic layer) and reaches the back plate (i.e., the carbon fiber toughened boron carbide composite material layer), thereby improving the anti-ballistic effect of the double-layer anti-ballistic structure.
[0029] In the carbon fiber toughened boron carbide composite material layer provided by the present invention, as the pyrolytic carbon thickness of the first group, the second group, the third group, and the fourth group of carbon fiber cloths, as well as the heat treatment temperature and time increase, the carbon fiber toughened boron carbide composite material layer can show the characteristic of increasing fracture toughness from the first group to the fourth group of carbon fiber cloths, which helps to further improve the anti-ballistic effect of the double-layer anti-ballistic structure.
[0030] The present invention deposits pyrolytic carbon on the carbon fiber cloth, which can significantly improve the surface smoothness of the carbon fiber and improve the fracture toughness of the prepared carbon fiber toughened boron carbide composite material; in addition, high-temperature heat treatment can increase the graphitization degree of the pyrolytic carbon, thereby improving the lubricity of the pyrolytic carbon, which helps to further improve the fracture toughness of the prepared composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The present invention is a flow chart for preparing the double-layer structure gradient boron carbide composite anti-ballistic product.
[0032] Figure 2 This is a cross-sectional geometric diagram of the stripes processed on the back side of the boron carbide ceramic panel of the present invention.
[0033] Figure 3 This is an electron micrograph of the cross section of the carbon fiber before pyrolytic carbon is deposited on the surface of the carbon fiber cloth of the present invention.
[0034] Figure 4 This is an electron micrograph of the cross section of the carbon fiber after pyrolytic carbon is deposited on the surface of the carbon fiber cloth of the present invention.
[0035] Figure 5 This is an electron micrograph of the cross section of the carbon fiber toughened boron carbide composite material prepared by the chemical vapor deposition method of the present invention.
[0036] Figure 6 This is a high-resolution transmission photograph of the interface of the carbon fiber toughened boron carbide composite material prepared by the chemical vapor deposition method of the present invention. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0038] In view of the low hardness and elastic modulus of fiber-reinforced polymer composite materials, which result in the inability to fully exert the double-layer structure to enhance the bullet-proof effect of bullet-proof products when used as a backboard, and the lack of a method for gradually increasing the fracture toughness of the backboard, the present invention provides a double-layer structured gradient boron carbide composite material, comprising a boron carbide ceramic layer and a carbon fiber toughened boron carbide composite material layer, and the layer is formed by combining a boron carbide deposition layer.
[0039] The carbon fiber toughened boron carbide composite material layer is composed of multiple groups of composite carbon fiber cloths, each group of composite carbon fiber cloths is composed of multiple carbon fiber cloths and pyrolytic carbon and boron carbide deposited on the surface of the carbon fiber cloths in sequence, and the thickness of the pyrolytic carbon increases in a direction away from the boron carbide ceramic layer in groups.
[0040] Furthermore, the thickness of the boron carbide deposition layer, i.e., the boron carbide deposited on the pyrolytic carbon on the surface of the carbon fiber cloth, is 60 to 90 μm.
[0041] In addition, the thickness of the pyrolytic carbon deposited on the surface of the carbon fiber cloth is 80 to 200 nm.
[0042] The thickness of the double-layer structure gradient boron carbide composite material is 26.5-29.8 mm, wherein the thickness of the boron carbide ceramic layer is 20 mm, and the thickness of the carbon fiber toughened boron carbide composite material layer is 6.5-9.8 mm.
[0043] The composite carbon fiber cloths are in 4 groups, and each group of composite carbon fiber cloths includes 6 to 9 carbon fiber cloths.
[0044] The thickness of pyrolytic carbon in the four groups of composite carbon fiber cloths, along the direction away from the boron carbide ceramic layer, is 80-110nm, 110-140nm, 140-170nm, and 170-200nm, respectively.
[0045] The above-mentioned double-layer structure gradient boron carbide composite material can effectively prevent the back plate from being separated from the face plate when the projectile penetrates the face plate (i.e., the boron carbide ceramic layer) and reaches the back plate (i.e., the carbon fiber toughened boron carbide composite material layer and the boron carbide deposition layer, denoted as carbon fiber toughened boron carbide ceramic-based composite material), thereby improving the anti-ballistic effect of the double-layer anti-ballistic structure.
[0046] Among them, the boron carbide ceramic panel is made by hot pressing or pressureless sintering, and the finished product can be purchased from the market.
[0047] The present invention also provides a method for preparing the double-layer structure gradient boron carbide composite material as claimed in claim 1, comprising the following steps:
[0048] (1) After chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, the cloth is placed in argon and subjected to high temperature heat treatment at 1760-1840° C. for 60-100 min to obtain a first composite carbon fiber cloth, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 80-200 nm.
[0049] (2) The first composite carbon fiber cloths with the same pyrolytic carbon thickness are taken as a group, and multiple groups of the first composite carbon fiber cloths are laid on the boron carbide ceramic layer with stripes in the order of increasing pyrolytic carbon thickness in the direction away from the boron carbide ceramic layer, and compacted to obtain a preform.
[0050] Among them, the cross section of the stripe is an isosceles trapezoid, such as Figure 2 As shown, the height of the isosceles trapezoid is 0.5-0.8 mm, the length of the upper side is 0.3-0.5 mm, and the length of the lower side is 0.9-1.2 mm.
[0051] (3) Chemical vapor deposition of boron carbide on the preform to obtain a double-layer structured gradient boron carbide composite material.
[0052] like Figure 1 As shown, the specific operations of the preparation method are as follows:
[0053] (1) The first group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1760 to 1780° C. for 60 to 70 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 80 to 110 nm;
[0054] The second group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1780 to 1800° C. for 70 to 80 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 110 to 140 nm;
[0055] The third group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1800 to 1820° C. for 80 to 90 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 140 to 170 nm;
[0056] The first composite carbon fiber cloth of the fourth group includes 6 to 9 carbon fiber cloths. After chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, the cloth is placed in argon and heat treated at 1820 to 1840°C for 90 to 100 minutes. The thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 170 to 200 nm.
[0057] The cross-sectional morphology of the carbon fiber before pyrolytic carbon deposition on the surface of the carbon fiber cloth is as follows: Figure 3 As shown, the cross-sectional morphology of the carbon fiber after pyrolytic carbon deposition on the surface of the carbon fiber cloth in group 2 is as follows Figure 4 As shown. It can be seen that when pyrolytic carbon is not deposited, the surface of the original carbon fiber is relatively rough ( Figure 3 ), deposition of pyrolytic carbon can significantly improve the surface smoothness of carbon fibers ( Figure 4 ), and improve the fracture toughness of the prepared composite material layer.
[0058] In addition, high temperature heat treatment can improve the graphitization degree of pyrolytic carbon, and then improve the lubricity of pyrolytic carbon, which helps to further improve the fracture toughness of the prepared composite material.
[0059] (2) Four groups of first composite carbon fiber cloths are laid on the boron carbide ceramic layer with stripes in the order of increasing pyrolytic carbon thickness in a direction away from the boron carbide ceramic layer, and compacted to obtain a preform.
[0060] With the increase of the pyrolytic carbon thickness of the first, second, third and fourth groups of carbon fiber cloths as well as the heat treatment temperature and time, the carbon fiber toughened boron carbide composite material backboard prepared by the present invention can show the characteristic of increasing fracture toughness from the first group to the fourth group of carbon fiber cloths, which helps to further improve the anti-ballistic effect of the double-layer anti-ballistic structure.
[0061] (3) Chemical vapor deposition of boron carbide on the preform, the boron carbide having a thickness of 60 to 90 μm, and polishing and smoothing to obtain a double-layer structured gradient boron carbide composite material.
[0062] The method provided by the present invention not only completes the preparation of the carbon fiber toughened boron carbide composite material layer, but also realizes the firm bonding of the boron carbide ceramic layer and the carbon fiber toughened boron carbide composite material layer. The obtained double-layer structure gradient boron carbide composite material can effectively avoid the separation of the back plate and the face plate when the projectile penetrates the face plate (i.e., the boron carbide ceramic layer) and reaches the back plate (i.e., the carbon fiber toughened boron carbide composite material layer and the boron carbide deposition layer, denoted as carbon fiber toughened boron carbide ceramic-based composite material), thereby improving the anti-ballistic effect of the double-layer anti-ballistic structure.
[0063] Compared with other preparation methods, the double-layer structured gradient boron carbide composite material prepared by chemical vapor deposition has the advantage of strong designability of mechanical properties. By adjusting the process parameters, the mechanical properties of the prepared composite material can be effectively adjusted to meet the ballistic requirements of anti-ballistic materials.
[0064] In addition, since the chemical vapor deposition method has the characteristic of net size molding, the preparation method of the present invention has the advantage of high yield.
[0065] The present invention also provides an application of the double-layer structure gradient boron carbide composite material in anti-bullet materials.
[0066] The double-layer structure gradient boron carbide composite material is used as an anti-ballistic product, wherein the boron carbide ceramic layer is the face plate, and the carbon fiber toughened boron carbide composite material layer and the boron carbide deposition layer are recorded as carbon fiber toughened boron carbide ceramic matrix composite material, which is used as a back plate and has a good anti-ballistic effect.
[0067] The present invention is described below in conjunction with an embodiment. The boron carbide ceramic panel used in the example was purchased from Shandong Huaen New Material Technology Co., Ltd. The density of the boron carbide ceramic panel was tested to be 2.51 g / cm 3 , compressive strength is 2900MPa, Vickers hardness is 29.5GPa, fracture toughness is 2.43MPa·m 1 / 2The carbon fiber cloth without pyrolytic carbon deposition (referred to as carbon cloth) used in the examples was purchased from Weihai Guangwei Composite Materials Co., Ltd. The carbon cloth was woven from carbon fiber numbered TZ300, with a tensile strength of 3530 MPa, a tensile elastic modulus of 230 GPa, an elongation at break of 1.5%, and a linear density of 198 g / km.
[0068] Example 1
[0069] (1) Stripes are uniformly processed on the back of the boron carbide ceramic panel. The cross section of the stripes is an isosceles trapezoid. The height of the trapezoid is 0.5 mm, the length of the upper side of the trapezoid is 0.5 mm, and the length of the lower side of the trapezoid is 1.2 mm;
[0070] (2) The carbon cloths were divided into 4 groups, each group including 9 carbon cloths, and pyrolytic carbon was deposited on each carbon cloth by chemical vapor deposition, wherein the pyrolytic carbon thicknesses of the carbon cloths in the first, second, third, and fourth groups were 80, 110, 140, and 170 nm, respectively;
[0071] (3) heat-treating the carbon cloth deposited with pyrolytic carbon in argon gas, wherein the heat treatment processes of the first, second, third and fourth groups of carbon cloth are heat-treated at 1780° C. for 60 min, 1800° C. for 70 min, 1820° C. for 80 min and 1840° C. for 90 min respectively;
[0072] (4) With the back side of the boron carbide ceramic panel facing upward, the first, second, third, and fourth groups of carbon cloth obtained in step (3) are laid flat on the boron carbide ceramic panel in sequence;
[0073] (5) placing a graphite block on the carbon cloth in step (4) to compact the carbon cloth and the boron carbide ceramic panel, and performing chemical vapor deposition of boron carbide on the carbon cloth and the boron carbide ceramic panel in step (4), controlling the boron carbide deposition thickness on the surface of the carbon cloth to be 60 μm;
[0074] (6) Grinding and smoothing the surface of the sample obtained in step (5) using a grinder to obtain the double-layer structure gradient boron carbide composite anti-ballistic product of the present invention.
[0075] The cross-sectional morphology of boron carbide deposited by chemical vapor deposition is shown in Figure 2. Figure 5 As shown, the high-resolution transmission photo of the interface of group 2 is as follows Figure 6 shown.
[0076] Example 2
[0077] (1) Stripes are evenly processed on the back of the boron carbide ceramic plate. The cross section of the stripes is an isosceles trapezoid. The height of the trapezoid is 0.6 mm, the length of the upper side of the trapezoid is 0.4 mm, and the length of the lower side of the trapezoid is 1.1 mm;
[0078] (2) The carbon cloths were divided into 4 groups, each group including 8 carbon cloths, and pyrolytic carbon was deposited on each carbon cloth by chemical vapor deposition, wherein the pyrolytic carbon thicknesses of the carbon cloths in the first, second, third, and fourth groups were 90, 120, 150, and 180 nm, respectively;
[0079] (3) The carbon cloth on which the pyrolytic carbon was deposited was heat treated in argon gas, wherein the heat treatment processes of the first, second, third and fourth groups of carbon cloth were heat treated at 1760° C. for 70 min, at 1790° C. for 75 min, at 1810° C. for 85 min and at 1820° C. for 100 min respectively;
[0080] (4) With the back side of the boron carbide ceramic panel facing upward, the first, second, third, and fourth groups of carbon cloth obtained in step (3) are laid flat on the boron carbide ceramic panel in sequence;
[0081] (5) placing a graphite block on the carbon cloth in step (4) to compact the carbon cloth and the boron carbide ceramic panel, and performing chemical vapor deposition of boron carbide on the carbon cloth and the boron carbide ceramic panel in step (4), controlling the boron carbide deposition thickness on the surface of the carbon cloth to be 70 μm;
[0082] (6) Grinding and smoothing the surface of the sample obtained in step (5) using a grinder to obtain the double-layer structure gradient boron carbide composite anti-ballistic product of the present invention.
[0083] Example 3
[0084] (1) Stripes are evenly processed on the back of the boron carbide ceramic plate. The cross section of the stripes is an isosceles trapezoid. The height of the trapezoid is 0.7 mm, the length of the upper side of the trapezoid is 0.4 mm, and the length of the lower side of the trapezoid is 1.0 mm.
[0085] (2) The carbon cloths were divided into 4 groups, each group including 7 carbon cloths, and pyrolytic carbon was deposited on each carbon cloth by chemical vapor deposition, wherein the pyrolytic carbon thicknesses of the carbon cloths in the first, second, third, and fourth groups were 100, 130, 160, and 190 nm, respectively;
[0086] (3) heat-treating the carbon cloth deposited with pyrolytic carbon in argon gas, wherein the heat treatment processes of the first, second, third and fourth groups of carbon cloth are heat-treated at 1770° C. for 65 min, heat-treated at 1780° C. for 80 min, heat-treated at 1800° C. for 90 min and heat-treated at 1830° C. for 95 min respectively;
[0087] (4) With the back side of the boron carbide ceramic panel facing upward, the first, second, third, and fourth groups of carbon cloth obtained in step (3) are laid flat on the boron carbide ceramic panel in sequence;
[0088] (5) placing a graphite block on the carbon cloth in step (4) to compact the carbon cloth and the boron carbide ceramic panel, and performing chemical vapor deposition of boron carbide on the carbon cloth and the boron carbide ceramic panel in step (4), controlling the boron carbide deposition thickness on the surface of the carbon cloth to be 80 μm;
[0089] (6) Grinding and smoothing the surface of the sample obtained in step (5) using a grinder to obtain the double-layer structure gradient boron carbide composite anti-ballistic product of the present invention.
[0090] Example 4
[0091] (1) Stripes are evenly processed on the back of the boron carbide ceramic plate. The cross section of the stripes is an isosceles trapezoid. The height of the trapezoid is 0.8 mm, the length of the upper side of the trapezoid is 0.3 mm, and the length of the lower side of the trapezoid is 0.9 mm.
[0092] (2) The carbon cloths were divided into 4 groups, each group including 6 carbon cloths, and pyrolytic carbon was deposited on each carbon cloth by chemical vapor deposition, wherein the thickness of pyrolytic carbon in the first, second, third and fourth groups of carbon cloths were 110, 140, 170 and 200 nm, respectively;
[0093] (3) heat-treating the carbon cloth deposited with pyrolytic carbon in argon gas, wherein the heat treatment processes of the first, second, third and fourth groups of carbon cloth are heat-treated at 1770° C. for 65 min, heat-treated at 1780° C. for 80 min, heat-treated at 1820° C. for 80 min and heat-treated at 1820° C. for 100 min respectively;
[0094] (4) With the back side of the boron carbide ceramic panel facing upward, the first, second, third, and fourth groups of carbon cloth obtained in step (3) are laid flat on the boron carbide ceramic panel in sequence;
[0095] (5) placing a graphite block on the carbon cloth in step (4) to compact the carbon cloth and the boron carbide ceramic panel, and performing chemical vapor deposition of boron carbide on the carbon cloth and the boron carbide ceramic panel in step (4), controlling the boron carbide deposition thickness on the surface of the carbon cloth to be 90 μm;
[0096] (6) Grinding and smoothing the surface of the sample obtained in step (5) using a grinder to obtain the double-layer structure gradient boron carbide composite anti-ballistic product of the present invention.
[0097] It is particularly noted that in the above embodiments, step (1) and step (2) both belong to the material preparation stage and there is no strict order of precedence.
[0098] Experimental Results
[0099] Since the mechanical properties of the panel are fixed, in order to accurately know the mechanical properties of the carbon fiber toughened boron carbide ceramic composite material prepared in Examples 1 to 4, the panel of the samples prepared in Examples 1 to 4 was removed, and only the mechanical properties of the back plate (i.e., the carbon fiber toughened boron carbide composite material layer and the boron carbide deposition layer, recorded as carbon fiber toughened boron carbide ceramic matrix composite material) were tested. Among them, the density test adopted the Archimedes drainage method, and the tensile strength test adopted the universal mechanical testing machine.
[0100] The test results are shown in Table 1.
[0101] Table 1 Backplane performance test results
[0102]
[0103] The density of dense boron carbide ceramic is about 2.52g / cm 3 The linear density of the carbon fiber used in the present invention is 198g / km. Since the density of carbon fiber is smaller than that of boron carbide, from Example 1 to Example 4, as the number of carbon cloth layers decreases and the thickness of chemical vapor deposited boron carbide increases, the density of the composite material increases from 1.92g / cm 3 Gradually increased to 2.01g / cm 3 In addition, the physical and mechanical properties of the composite material are also gradually changing. Specifically, the interlaminar tensile strength gradually increases from 243MPa to 298MPa, and the maximum fracture toughness increases from 14.3MPa·m 1 / 2 Gradually increased to 15.3MPa·m 1 / 2 , the minimum fracture toughness is 11.5MPa·m 1 / 2 Gradually increased to 12.4MPa·m 1 / 2 It can be seen that the fracture toughness of the composite material back panel is much higher than that of the boron carbide ceramic panel, and the fracture toughness of the composite material back panel has the characteristics of gradient change.
[0104] The double-layer structure gradient boron carbide composite bullet-resistant products of Examples 1 to 4 were subjected to a target shooting test. During the test, the boron carbide ceramic plate was used as the bullet-facing surface, the carbon fiber toughened boron carbide ceramic composite material was used as the back bullet surface, a 56-type semi-automatic rifle and a 7.62mm armor-piercing incendiary bullet were used, the initial velocity of the bullet was about 650m / s, the target shooting distance was 15m, and 3 samples were tested for each example, and the sample with the worst performance was conservatively used as the bullet-resistant evaluation result.
[0105] In addition, three comparative examples are provided to compare the target shooting effects of Examples 1 to 4.
[0106] In Comparative Example 1, a target shooting test was performed on a boron carbide ceramic plate having a thickness of 20 mm.
[0107] In Comparative Example 2, a target shooting test was performed on a boron carbide ceramic plate having a thickness of 30 mm.
[0108] In Comparative Example 3, compared with Example 1, no panel is used, each group of carbon fiber cloth has 27 sheets, and the treatment of the four groups of carbon fiber cloth is the same as that of Example 1. A carbon fiber reinforced boron carbide ceramic composite material with a thickness of 30 mm is prepared, and a target shooting test is performed on the composite material.
[0109] The test results are shown in Table 2.
[0110] Table 2 Target shooting test results
[0111] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Total thickness(mm) 29.8 28.7 27.6 26.5 20 30 30 Panel thickness (mm) 20 20 20 20 20 30 - Back panel thickness (mm) 9.8 8.7 7.6 6.5 0 0 30 Back convex(mm) 3.6 4.1 4.5 4.7 - - 13.2 Implementation Effect Not penetrated Not penetrated Not penetrated Not penetrated penetrate penetrate penetrate
[0112] It can be seen from Comparative Example 1 that bullets can penetrate a 20mm thick boron carbide ceramic plate. From Example 1 to Example 4, as the number of carbon cloth layers in each group decreases, although the back plate thickness of the sample gradually decreases from 9.8mm to 6.5mm, and the total thickness of the sample gradually decreases from 29.8mm to 26.5mm, all samples show excellent anti-ballistic effects. Specifically, all samples are not penetrated by bullets, and the back convexity is very small. From Example 1 to Example 4, the back convexity of the sample only gradually increases from 3.6mm to 4.7mm.
[0113] As can be seen from Comparative Example 2, the boron carbide ceramic plate is still unable to resist the penetration of bullets even when the thickness is increased from 20 mm to 30 mm. In addition, as can be seen from Comparative Example 3, the composite material with a thickness of 30 mm is not only unable to resist the penetration of bullets, but also has a back convexity of up to 13.2 mm.
[0114] It can be seen from the above embodiments and comparative examples that the double-layer structure gradient boron carbide composite anti-ballistic product prepared by the method of the present invention not only has excellent anti-ballistic effect, but also has the characteristics of being thinner and lighter.
Claims
1. A double-layer structure gradient boron carbide composite material, characterized in that: It includes a boron carbide ceramic layer and a carbon fiber toughened boron carbide composite material layer, and is formed by combining the boron carbide deposition layer; The carbon fiber toughened boron carbide composite material layer is composed of multiple groups of composite carbon fiber cloths, each group of composite carbon fiber cloths is composed of multiple carbon fiber cloths and pyrolytic carbon and boron carbide deposited on the surface of the carbon fiber cloths in sequence, and the thickness of the pyrolytic carbon increases in a direction away from the boron carbide ceramic layer in groups.
2. The double-layer structure gradient boron carbide composite material according to claim 1, characterized in that: The thickness of the boron carbide deposition layer, the boron carbide deposited on the pyrolytic carbon on the surface of the carbon fiber cloth, is 60 to 90 μm.
3. The double-layer structure gradient boron carbide composite material according to claim 1, characterized in that: The thickness of the pyrolytic carbon deposited on the surface of the carbon fiber cloth is 80 to 200 nm.
4. The double-layer structure gradient boron carbide composite material according to claim 1, characterized in that: The thickness of the double-layer structure gradient boron carbide composite material is 26.5-29.8 mm, wherein the thickness of the boron carbide ceramic layer is 20 mm, and the thickness of the carbon fiber toughened boron carbide composite material layer is 6.5-9.8 mm.
5. The double-layer structure gradient boron carbide composite material according to claim 1, characterized in that: The composite carbon fiber cloths are in 4 groups, and each group of composite carbon fiber cloths includes 6 to 9 carbon fiber cloths.
6. The double-layer structure gradient boron carbide composite material according to claim 5, characterized in that: The thickness of pyrolytic carbon in the four groups of composite carbon fiber cloths, along the direction away from the boron carbide ceramic layer, is 80-110nm, 110-140nm, 140-170nm, and 170-200nm, respectively.
7. A method for preparing the double-layer structure gradient boron carbide composite material as claimed in claim 1, characterized in that: The following steps are involved: (1) After chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, the cloth is placed in argon gas and subjected to high temperature heat treatment at 1760-1840° C. for 60-100 min to obtain a first composite carbon fiber cloth, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 80-200 nm; (2) taking a first composite carbon fiber cloth having the same pyrolytic carbon thickness as a group, laying a plurality of groups of first composite carbon fiber cloths on the boron carbide ceramic layer having stripes in the order of increasing pyrolytic carbon thickness in a direction away from the boron carbide ceramic layer, and compacting them to obtain a preform; (3) Chemical vapor deposition of boron carbide on the preform to obtain a double-layer structured gradient boron carbide composite material.
8. The method for preparing the double-layer structure gradient boron carbide composite material according to claim 7, characterized in that: The operation is as follows: (1) The first group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1760 to 1780° C. for 60 to 70 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 80 to 110 nm; The second group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1780 to 1800° C. for 70 to 80 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 110 to 140 nm; The third group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1800 to 1820° C. for 80 to 90 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 140 to 170 nm; The fourth group of first composite carbon fiber cloths includes 6 to 9 carbon fiber cloths, each of which is subjected to chemical vapor deposition of pyrolytic carbon on the surface of each carbon fiber cloth, and then placed in argon gas and heat treated at 1820 to 1840° C. for 90 to 100 minutes, wherein the thickness of the pyrolytic carbon on the surface of each carbon fiber cloth is 170 to 200 nm; (2) laying four groups of first composite carbon fiber cloths in order of increasing pyrolytic carbon thickness in a direction away from the boron carbide ceramic layer, and pressing them to obtain a preform; (3) Chemical vapor deposition of boron carbide on the preform, wherein the thickness of the boron carbide is 60 to 90 μm, thereby obtaining a double-layer structured gradient boron carbide composite material.
9. The method for preparing the double-layer structure gradient boron carbide composite material according to claim 7, characterized in that: In the step (2), the cross section of the stripe is an isosceles trapezoid, the height of the isosceles trapezoid is 0.5-0.8 mm, the length of the upper side is 0.3-0.5 mm, and the length of the lower side is 0.9-1.2 mm.
10. Use of the double-layer structure gradient boron carbide composite material as claimed in claim 1 in anti-ballistic materials.
Citation Information
Patent Citations
Bulletproof composite armor and preparation method thereof
CN111238309A
Ceramic material with layered structure
CN111620695A
Carbon fiber cloth-reinforced boron carbide composite material as well as preparation method and application thereof
CN111892402A
Gradient ceramic column reinforced aluminum-based composite armor plate and preparation method
CN113983868A
Layered bulletproof ceramic and preparation method thereof
CN114349515A